2020
DOI: 10.1002/cctc.202001423
|View full text |Cite
|
Sign up to set email alerts
|

Confined Ru Nanocatalysts on Surface to Enhance Ammonia Synthesis: An In situ ETEM Study

Abstract: Ammonia is an important feedstock for producing fertilizer and chemicals as well as is also a potential energy carrier. Generally, MgO is considered as an electronic promoter for Ru catalysts in ammonia synthesis. In this research, it was found for the first time that surface atoms of Ru particles are stabilized by MgO modification at high temperature and reaction atmosphere, which contained more highly active B5‐sites for ammonia synthesis. Ex situ HRTEM images show similar Ru nanoparticles containing steps w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 69 publications
1
8
0
Order By: Relevance
“…These results demonstrate that the tuning of the anion of the support has a significant influence on NH 3 synthesis performance. Previous studies have demonstrated that the activity of Ru-based catalysts without a promoter is negligible, and the introduction of a proper promoter to the Ru-based catalyst would enhance NH 3 synthesis. , Herein, different promoters, such as K, Ba, and Cs, were introduced into best-performing Ru/ZrH 2 . Among them, Ba exhibits an optimal promoting effect, and the NH 3 synthesis rate over Ba–Ru/ZrH 2 (5 wt % Ba) can reach up to 27.5 mmol g –1 h –1 , which is 3.1 times that of Ru/ZrH 2 (Figures a and S2).…”
Section: Resultsmentioning
confidence: 99%
“…These results demonstrate that the tuning of the anion of the support has a significant influence on NH 3 synthesis performance. Previous studies have demonstrated that the activity of Ru-based catalysts without a promoter is negligible, and the introduction of a proper promoter to the Ru-based catalyst would enhance NH 3 synthesis. , Herein, different promoters, such as K, Ba, and Cs, were introduced into best-performing Ru/ZrH 2 . Among them, Ba exhibits an optimal promoting effect, and the NH 3 synthesis rate over Ba–Ru/ZrH 2 (5 wt % Ba) can reach up to 27.5 mmol g –1 h –1 , which is 3.1 times that of Ru/ZrH 2 (Figures a and S2).…”
Section: Resultsmentioning
confidence: 99%
“…It could be suggested that the dissociative route of NH 3 synthesis is preferred over the Ru sites, consistent with previous studies. 18,19 Moreover, in the case of the reaction over the nitrogen vacancy of TiCN (Figures 5b and S22b), the N 2 adsorbed on the vacancy is more activated and the N−N bond distance is much longer (1.46 Å) due to the electrons captured in the vacancy. Therefore, as electrons transfer from the adjacent Ti and Ru atoms (Figure S23b), the Bader charge of the absorbed N 2 (−2.48|e|) is more negative than for Ru active sites and the π*-N 2 orbitals are more stabilized with obvious interaction with TiCN below the Fermi level (Figure S24).…”
Section: Identification Of the Dissociative Mechanismmentioning
confidence: 99%
“…Nevertheless, the activation of N 2 largely relies on the availability of nitride vacancy formation, and NH 3 is only generated on metal nitride, which in some degree constrains the catalytic performance. On the other hand, Ru-based catalysts as the second-generation catalysts for ammonia synthesis are capable of facile dissociation of the NN triple bond on Ru B 5 -stepped sites via a dissociative route. , Taking advantage of the metal nitride and Ru metal for N 2 activation, we envisage that a Ru-based catalyst promoted by an appropriate titanium carbonitride (TiCN) (TiC 0.5 N 0.5 , denoted as TiCN) might result in active sites for N 2 activation via both dissociative and associative routes, a strategy for NH 3 synthesis that has not been reported before. It is pivotal to determine the simultaneous occurrence of the two routes and to clarify whether the synergistic mechanism enhances the catalytic performance under mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, the methanation of carbon supports during the reaction leads to the metal sintering and then the loss of active B5 sites . As shown in Figure b, it is found that the Ru atoms on the edges and steps of Ru NPs could be stabilized by MgO modification under high temperatures, which remained active B5 sites for ammonia synthesis . Moreover, the further incorporation of CsO x promoted the electron donation and then enhance the ammonia synthesis rate, which is 5-fold higher than MgO-Ru/MS.…”
Section: Ammonia Synthesis Over Ru-based Catalystsmentioning
confidence: 99%